Simplifying the following expression: 15 + w +(– 12) = 15 – 12 + w

Question

Simplifying the following expression:

15 + w +(– 12) = 15 – 12 + w

in progress 0
Dulcie 2 months 2021-09-02T15:43:28+00:00 2 Answers 0 views 0

Answers ( )

    0
    2021-09-02T15:44:51+00:00

    Explination:

    5 + w +(– 12) = 15 – 12 + w

    5+(-12)=15-12

    -7 = 3

    Answer: -7 = 3

    0
    2021-09-02T15:45:00+00:00

    Answer:

    I think it is 0

    Step-by-step explanation:

Leave an answer

Browse

Giải phương trình 1 ẩn: x + 2 - 2(x + 1) = -x . Hỏi x = ? ( )